Pelaksanaan Metode Drill Dalam Meningkatkan Kemampuan Membaca Al-Qur’an Siswa - Pepilasari, Reka; Rahman, Rini (Prodi Pendidikan Keagamaan Islam, 2025)
This research aims to examine the implementation of the Drill method in improving students' Al-Qur'an reading skills at the Padang State Agricultural Development Vocational School. The Drill method, which emphasizes repeated practice, has been implemented by Islamic Religious Education teachers since 2022 and has shown positive results. This research uses a qualitative approach with descriptive methods, data collection techniques in the form of observation, interviews and documentation. The research results show that the application of the Drill method is carried out consistently at two times, namely during PAI lessons and break times. The implementation stages include initial activities (prayer and preparation), core activities (getting to know the hijaiyah letters, understanding the science of recitation, and practicing reading verses repeatedly), and closing activities. With this method, students experience an increase in fluency, pronunciation of makhraj letters, and understanding of the rules of recitation. This research concludes that the Drill method is effective in significantly improving students' Al-Qur'an reading skills.